The Transcriptional Role of Vitamin A and the Retinoid Axis in Brown Fat Function - Herz, Carsten T.; Kiefer, Florian W. (Frontiers in Endocrinology, 2020)
In recent years, brown adipose tissue (BAT) has gained significance as a metabolic organ dissipating energy through heat production. Promotion of a thermogenic program in fat holds great promise as potential therapeutic tool to counteract weight gain and related sequelae. Current research efforts are aimed at identifying novel pathways regulating brown fat function and the transformation of white adipocytes into BAT-like cells, a process called "browning". Besides numerous genetic factors some circulating molecules can act as mediators of adipose tissue thermogenesis. Vitamin A metabolites, the retinoids, are potent regulators of gene transcription through nuclear receptor signaling and are thus involved in a plethora of metabolic processes. Accumulating evidence links retinoid action to brown fat function and browning of WAT mainly via orchestrating a transcriptional BAT program in adipocytes including expression of key thermogenic genes such as uncoupling protein 1. Here we summarize the current understanding how retinoids play a role in adipose tissue thermogenesis through transcriptional control of thermogenic gene cassettes and potential non-genomic mechanisms.